2010
DOI: 10.1177/0969733009355372
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of end-of-life education among community-dwelling older adults

Abstract: The purpose of this study was to evaluate the effectiveness of an educational intervention regarding end-of-life discussion directed at older Japanese adults and their attitude to and acceptance of this intervention. A quasi-experimental design was used. A total of 121 older adults, aged 65 years and over, consented to participate. Data from 55 intervention and 57 control participants were used for the analysis. The intervention consisted of an education program comprising a video, a lecture using a handout, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
0
32
1
Order By: Relevance
“…As noted in prior education with older adults (Matsui, 2010;Rigdon, 2009), participants valued the use of multiple teaching methods that corresponded and supported each other. For example, written handouts that reiterated the facts stated and complimented the didactic information were greatly appreciated.…”
Section: Organizationmentioning
confidence: 91%
“…As noted in prior education with older adults (Matsui, 2010;Rigdon, 2009), participants valued the use of multiple teaching methods that corresponded and supported each other. For example, written handouts that reiterated the facts stated and complimented the didactic information were greatly appreciated.…”
Section: Organizationmentioning
confidence: 91%
“…[789] A recent study in Japan showed that EOL discussion in healthy elderly patients led to more acceptance of advanced directives and less preference of artificial nutrition as the life-sustaining measure. [10] The likelihood of EOL discussion also depends on factors specific to the patients (e.g., age and comorbidity) and to the care providers (e.g., training status and time constraints). One study among healthy older adults showed that patients with recent hospitalization[11] or bereavement from death of a loved one[1112] often facilitated EOL discussions.…”
Section: Discussionmentioning
confidence: 99%
“…19,27 The person benefits from engaging in a personal inventory on acceptable states and valued activities as the central focus and how these are supported or compromised by different proposed interventions or treatment options. 20,27 Ko and Lee 31 found higher knowledge of ACP, greater experience with illness and decision-making for loved ones, and perceived severity were strong predictors of end-of-life communication. Higher education has also been suggested to correlate with an increased incidence of having advance directives, and culture has also demonstrated an impact, 23,24,26,28,29 with white populations more likely to complete advance directives and discuss ACP with health agencies than other cultures.…”
Section: An Individualized Approachmentioning
confidence: 97%
“…[20][21][22] Acknowledgment of the ongoing process with an inherent requirement to regularly revisit and review care preferences as things Ludwick and Baughman 13 Mazzocato et al 15 Heiman et al 16 Dexter et al 17 Yung et al 18 Schiebel et al 19 Matsui 20 Allen et al 21 Tierney et al 22 McCarthy et al 23 An individualized approach Heiman et al 16 Schiebel et al 19 Matsui 20 Allen et al 21 Hopp 24 Seymour et al 25 Kahana et al 26 Department of Health 27 Rosenfeld et al 28 Collaborative engagement Dexter et al 17 Yung et al 18 Schiebel et al 19 Allen et al 21 Tierney et al 22 Hopp 24…”
Section: Information That Needs To Be Shared In An Eacp: Acp As a Promentioning
confidence: 97%
See 1 more Smart Citation